Genetic basis of Alzheimer's dementia: role of mtDNA mutations - Grazina, M. (2006)
Alzheimer's disease (AD) is the most common neurodegenerative disorder associated to dementia in late adulthood. Amyloid precursor protein, presenilin 1 and presenilin 2 genes have been identified as causative genes for familial AD, whereas apolipoprotein E 6034 allele has been associated to the risk for late onset AD. However, mutations on these genes do not explain the majority of cases. Mitochondrial respiratory chain (MRC) impairment has been detected in brain, muscle, fibroblasts and platelets of Alzheimer's patients, indicating a possible involvement of mitochondrial DNA (mtDNA) in the aetiology of the disease. Several reports have identified mtDNA mutations in Alzheimer's patients, suggesting the existence of related causal factors probably of mtDNA origin, thus pointing to the involvement of mtDNA in the risk contributing to dementia, but there is no consensual opinion in finding the cause for impairment. However, mtDNA mutations might modify age of onset, contributing to the neurodegenerative process, probably due to an impairment of MRC and/or translation mechanisms.